Symptom burden and surgical outcome in non-skull base meningiomas - Mederer, Tobias; Schachinger, Sebastian; Rosengarth, Katharina; Brosig, Anja; Schebesch, Karl-Michael; Doenitz, Christian; Schmidt, Nils-Ole; Proescholdt, Martin Andreas (Frontiers in Oncology, 2022)
Purpose: Non-skull base meningiomas (NSBM) are a distinct entity and frequently present with focal neurological deficits. This study was designed to analyze functional and oncological outcome following microsurgical tumor resection in patients with NSBM. Patients and methods: An analysis of 300 patients that underwent NSBM resection between 2003 and 2013 was performed. Assessment measures for functional outcome were Karnofsky Performance Scale (KPS), Medical Research Council - Neurological Performance Scale (MRC-NPS), and improvement rates of focal deficits and seizures. The extent of resection; recurrence-free survival (RFS) and tumor-specific survival (TSS) were also determined. Results: Impaired KPS and MRC-NPS were present in 73.3% and 45.7%, respectively. Focal neurological deficits were recorded in 123 patients (41.0%), with hemiparesis (21.7%) and aphasia (9.3%) the most prevalent form of impairment. Most meningiomas were localized at the convexity (64.0%), followed by falcine tumors (20.3%). Both KPI and MRC-NPS scores were significantly improved by surgical resection. Postoperative improvement rates of 96.6%, 89.3%, 72.3%, 57.9%, and 27.3% were observed for aphasia, epilepsy, hemiparesis, cranial nerve, and visual field deficits, respectively. Long-term improvement was achieved in 83.2%, 89.3%, 80.0%, 68.4% and 54.6% of patients, respectively. Gross total resection (GTR) over subtotal resection (STR) significantly improved preoperative seizures and visual field deficits and correlated with reduced risk of new postoperative hemiparesis. Poor Simpson grade was the only significant prognostic factor in multivariate analysis for long-term functional deficit, which occurred in 7.3%. Median RFS was 45.9 months (6.0 - 151.5 months), while median TSS was 53.7 months (3.1 – 153.2 months). Both WHO grade (p= 0.001) and Simpson classification (p= 0.014 and p= 0.031) were independent significant prognostic factors for decreased RFS and TSS by multivariate analysis, respectively. Furthermore, tumor diameter > 50 mm (p= 0.039) significantly correlated with decreased TSS in multivariate analysis. Conclusion: Surgical resection significantly and stably improves neurological deficits in patients with NSBM.